Proceedings of the European Computing Conference Volume 2 - Mastorakis, Nikos; Mladenov, Valeri; Kontargyri, Vassiliki T.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
These two volumes are from proceedings of the European Computing Conference. The conference focus was in the areas of Systems Theory, Applied Mathematics, Simulation, Numerical and Computational Methods, and Parallel Computing, which was held September 25-27, 2007 in Athens, Greece. Each volume is divided into sections that focus on different topics. The first volume includes seven sections with topics ranging from neural networks and applications to educational software and e-learning. The second volume has eight sections covering topics such as computer applications in power systems and theoretical approaches in information science. All the chapters are self-contained and peer reviewed.
Computer Applications in Power Systems -- Wind Energy Production Forecasting -- Operation Management on Autonomous Power System -- A Low-Power Portable H.264/AVC Decoder Using Elastic Pipeline -- Computational Techniques and Algorithms -- Computational Methods for Detecting Types of Nonlinear Dynamics -- The Worm Cutter Tool Profiling Based on Discreet Surfaces Representation -- Suggesting Correct Words Algorithms Developing in FarsiTeX -- On the Analytical and Numerical Computation in Mechanical Modeling -- Real Genetic Algorithm for Traveling Salesman Problem Optimization -- The COTECOMO: COnstractive Test Effort COst MOdel -- A Semantics of Core Computational Model for ODP Specifications -- Computer Simulation Via Direct Modeling -- Image Segmentation with Improved Artificial Fish Swarm Algorithm -- Propagation of Elastic-Plastic Waves in Bars -- Shahyat Algorithm as a Clustering Method -- A Modified Electromagnetism-Like Algorithm Based on a Pattern Search Method -- Latency Hiding and Adaptability for Parallel Iterative Algorithms -- Clustering the Linearly Inseparable Clusters -- A Top-Down Minimization Algorithm for Non-Deterministic Systems -- Natural Phenomena and Computer Models -- Multi-Layer Finite Volume Solution of Wind Induced Basin Flow -- NASIR Heat Generation and Transfer Solver for RCC Dams -- Water Hammer Modeling Using 2nd Order Godunov Finite Volume Method -- Simulation of Wind Pressure on Two Tandem Tanks -- Tropical Cyclone Forecaster Integrated with Case-Based Reasoning -- Knowledge Engineering, Decision Rules and Data Bases -- Toward an Understanding of Knowledge Reuse in an On-Line Environment -- Handling Contradictions in Knowledge Discovery Applications -- A Cooperative Distributed Query-Processing Approach -- Estimating Join and Projection Selectivity Factors -- Decision Rules: A Metamodel to Organize Information -- A Computerized Solution for the Financial Diagnose of the SMEs -- DELP System: Tracking Deadlocks and Phantoms in Databaseas -- Concurrency Control for Multilevel Secure Distributed Real-Time Databases -- A New Framework for Nondeterministic Multi-valued System Minimization -- Web-Based Applications -- Thread Pool-Based Improvement of the Mean-Value Analysis Algorithm -- Security Enhancements for Web-Based Applications -- Description and Discovery of Web Applications in Grid -- An Approach to Treat the User's Preferences About Personal Data -- Ssort: Peak Analysis for Efficient String Sorting -- Parametric Studies for the AEC Domain Using InteliGrid Platform -- An Auction-Based Resource Allocation Strategy with a Proportional Share Model for Economic-Based Grid Systems -- Advances in Computer Science and Applications -- Propagation in Cylindrical Inset Dielectric Guide Structures -- On the Damage in Nonlinear Mesoscopic Materials -- Diagnosis of Robotized Assembling Systems -- Open Architecture Systems for MERO Walking Robots Control -- Mass Transfer Analysis in the Case of the EFG Method -- Information System Architecture for Data Warehousing -- Dimensional Dynamics Identification of Reconfigurable Machine Tools -- Compaction-Induced Deformation on Flexible Substrate -- Robust and Accurate Visual Odometry by Stereo -- Financial Auditing in an E-Business Environment -- Reputed Authenticated Routing Ad-Hoc Networks Protocol -- Quantum Mechanical Analysis of Nanowire FETs -- Software Tools and Programming Languages -- Impact of Quality Factors on the Success of Software Development -- Sisal 3.2 Language Structure Decomposition -- An Embedded Application for Driverless Metro Train -- A Post-mortem JavaSpaces Debugger -- Stochastic Numerical Simulations Using C# -- Visualization and Analyses of Multi-Dimensional Data Sets Using OLAP- A Case Study of a Student Administration System -- Design of a Computer-Based Triangle Chess Machine -- A Taxonomy Model for Analyzing Project-Based Learning Using Analytical Hierarchy Process (AHP): A Case Study of Design of a Beer Company Website in an Elementary School -- A Framework of Mixed Model of a Neural Network and Boolean Logic for Financial Crisis Prediction -- Chinese Document Clustering Using Self-Organizing Map-Based on Botanical Document Warehouse -- Linear Discriminant Analysis in Ottoman Alphabet Character Recognition -- User Requirements Engineering and Management in Software Development -- SSAF - A Tool for Active Filter Synthesis -- Theoretical Approaches in Information Science -- On the Complexity of the Auxetic Systems -- New Verification of Reactive Requirement for Lyee Method -- A Tree Derivation Procedure for Multivalent and Paraconsistent Inference -- On the Feedback Stabilization of Matrix -- Maxwell Geometric Dynamics -- Fractional Right Ideals -- A Distributed Approach for Concurrent Password Recovery of Archived Files -- Solutions for an Integral-Differential Equation -- Development of Genetic Algorithms and C-Method for Optimizing a Scattering by Rough Surface.
Keywords: ENGINEERING; COMPUTER NETWORK ARCHITECTURES; COMPUTER COMMUNICATION NETWORKS; ARTIFICIAL INTELLIGENCE; COMPUTER ENGINEERING; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; COMPUTER COMMUNICATION NETWORKS; SIGNAL, IMAGE AND SPEECH PROCESSING; ARTIFICIAL INTELLIGENCE (INCL. ROBOTICS).; ELECTRICAL ENGINEERING; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS